Pemberdayaan Kesehatan Mental Perempuan melalui Terapi Dzikir pada Komunitas Literasi Daring: - - Marmi Marmi; Lina Siti Nuryawati; Rina Nuraeni; Ade Tedi Irawan (JOURNAL OF PHILANTHROPY: The Journal of Community Service, 2026)
Women’s mental health in the digital era faces complex challenges, particularly psychological stress arising from multiple role demands and intensive online engagement. This community service activity aimed to empower women’s mental health through mental health education and dhikr-based therapy within an online literacy community, namely a women-dominated online book discussion community consisting of adult female members who actively participate in regular digital literacy activities. The program was conducted online in December 2025 and involved 20 active participants out of 30 invited members, with inclusion criteria of adult women who were active community members and willing to participate fully in the intervention. The methods included interactive mental health education, guided dhikr therapy practice using the istighfar recitation (astagfirullahal‘adhiim), and evaluation through pretest–posttest stress assessments accompanied by qualitative feedback. The results indicated an improvement in participants’ understanding of stress management and a descriptive decrease in stress levels following the intervention. Qualitative feedback further revealed enhanced inner calmness, emotional awareness, and perceived coping capacity in daily digital activities. These findings suggest that integrating mental health education with psycho-spiritual approaches within an online literacy community has the potential to serve as an adaptive and sustainable empowerment strategy to support women’s mental well-being.